A Prospective, Multicentre, Open-Label Single-Arm Exploratory Study to Evaluate Efficacy and Safety of Saroglitazar on Hypertriglyceridemia in HIV Associated Lipodystrophy - Deshpande, Alka; Toshniwal, Harsh; Joshi, Shashank; Jani, Rajendrakumar H. (PLOS ONE, 2016)
Objective This study was designed to explore the efficacy and safety of saroglitazar 4 mg on hypertriglyceridemia in patients with HIV associated lipodystrophy. Methods During this 12-week prospective, multi-centric, open-label, single arm exploratory study, 50 patients were enrolled to receive saroglitazar 4 mg orally once daily in the morning before breakfast. The primary efficacy endpoint was the percent change in triglyceride (TG) levels from baseline to Week 6 and Week 12. The secondary efficacy endpoints were assessment of low-density-lipoprotein (LDL), very-low-density-lipoprotein (VLDL), high-density-lipoprotein (HDL), non-HDL cholesterol, total cholesterol, apo-lipoprotein (Apo) A1, Apo B, and C-peptide and fasting insulin for HOMA beta and HOMA IR. Safety assessment was performed during the study. Results Saroglitazar 4 mg significantly decreased the serum TG levels from baseline at Week 6 (percent change: -40.98; 95% CI: -50.82, -31.15) and Week 12 (percent change -45.11; 95% CI: -52.37, -37.86). Reduction in VLDL cholesterol (percent change: -46.33; 95% CI: -52.89, -39.76) and total cholesterol (percent change: 7.37; 95% CI: 1.96, 12.78) was observed at week 12 from baseline. Saroglitazar increased HDL cholesterol (percent change: 34.56, 95% CI: 22.22, 46.90), Apo A1 (percent change: 33.16; 95% CI: 18.69, 47.63) and Apo B (percent change: 10.55, 95% CI: 2.86, 18.25) levels at week 12 from baseline. Saroglitazar treatment led to increase in the C-peptide (percent change: 59.42, 95% CI: 48.78, 70.06), fasting insulin levels (percent change: 47.10; 95% CI: 38.63, 55.57), HOMA of beta cell function for C-peptide (percent change: 71.67; 95% CI: 39.09, 104.26) and HOMA of insulin resistance for C-peptide (percent change: 58.29, 95% CI: 46.74, 69.83) at week 12 from baseline. Saroglitazar treatment was safe and well tolerated in this study. Conclusion Overall, the observed changes in lipid profile after 12 weeks of saroglitazar treatment were in the direction of improvement in patients with HIV associated lipodystrophy. Trial Registration Clinical Trial Registry of India Phase II/CTRI/2010/091/000107